Research in consumer behaviour. Vol. 12 - Belk, Russell W. (Research in consumer behavior., 2010)
This volume presents recent consumer research across both positivist and interpretivist methods, focusing on topics with considerable current interest. These topics include organic food consumption, luxury goods consumption by Chinese consumers, country of manufacture effects on product quality perceptions, and the nature and effects of cool consumption. The perspectives embraced include managerial strategies, motivational mechanisms, social influences, and product and brand evaluations. Approximately half of the papers in the present volume were selected from those accepted for the 5th Annual Consumer Culture Theory Conference held at the University of Wisconsin in June of 2010. Together this latter set of interpretive papers presenting cutting edge interpretive consumer research. They also add to the richness of the topics covered in the volume, including chapters emphasizing brands, fashions, blogs, service receipt, and consumption experiences. They also add to the methodological scope of the volume, including uses of ethnography, autoethnography, netnography, and discourse analysis. Altogether the volume is a good reflection of what is happening in the field of consumer research.